2012
DOI: 10.4149/av_2012_04_283
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the envelope glycoproteins of foamy viruses

Abstract: Summary. -One of the most fascinating findings in retrovirology is the construction of viral vectors based on foamy viruses (FVs) for gene therapy. The envelope glycoprotein (Env), one of the structural proteins of FV, is an important antigen in the immunoassays, as it is highly specific. To compare the characteristics of all 15 available FV Envs, the phylogenesis, hydrophobicity, modifications, and conserved motifs were analyzed based on the Env sequences. Meanwhile, the secondary structures of transmembrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…Th e data revealed that there were three structural regions within gp47 subunits: two long helix regions at N-terminus and C-terminus respectively, and a long region of extended β-strands and loops in the middle. Th e results were similar to the previous analyses using a diff erent secondary structure prediction program (Sun et al, 2012).…”
Section: Solvent Accessibility and Secondary Structure Of Fvs Gp47supporting
confidence: 88%
See 3 more Smart Citations
“…Th e data revealed that there were three structural regions within gp47 subunits: two long helix regions at N-terminus and C-terminus respectively, and a long region of extended β-strands and loops in the middle. Th e results were similar to the previous analyses using a diff erent secondary structure prediction program (Sun et al, 2012).…”
Section: Solvent Accessibility and Secondary Structure Of Fvs Gp47supporting
confidence: 88%
“…Based on this motif, most FVs were observed budding predominantly at endomembranes (e.g., ER, Golgi). When the dilysine motif was missing, EFV was budded at the plasma membrane (Muñoz-Barroso et al, 1999;Lindemann and Rethwilm, 2011;Sun et al, 2012).…”
Section: Membrane-spanning Domain (Msd) Of Fvs Gp47mentioning
confidence: 99%
See 2 more Smart Citations
“…The number and position of N-glycosylation sites in FV Env differ from HIV-1 and MLV [32,33]. However, post-translational modifications such as the attachment of oligosaccharides to viral Env asparagine residues are not only known to promote proper folding or intracellular trafficking but also to ensure for specific interaction with receptor molecules (reviewed in [34]).…”
Section: Early Events In Virus-host Interaction: Attachment and Entrymentioning
confidence: 99%